Belgium : Technical Note on Crisis Management and Bank Resolution Framework. (IMF Staff Country Reports; Country Report ;, 2013)
The ability of the National Bank of Belgium (NBB) to provide emergency liquidity assistance to solvent but temporarily illiquid firms is well tested and satisfactory. Belgian authorities are testing draft guidelines for recovery plans through pilot projects with selected firms that are of systemic importance. Introducing recurrent crisis management simulations would allow the authorities to test the coordination arrangements and potential application of the crisis management toolkit. It is commended that the NBB can enhance the framework for orderly and effective resolution.